BEBERAPA FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI JAGUNG PIPILAN VARIETAS HIBRIDA BISI-2 (ZEA MAYS L) - Dety Sukmawati; Hendar Suhendar (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2015)
Farming activities of production facilities is important, because most new technologies that can increase agricultural production requires the use of means of production by farmers, while the production process includes corn farming, planting, fertilizing, maintenance, and pest and disease control. Seeds to be used should be of quality seed of improved varieties, and not mixed with others varieties. This Research is a case which is a survey on farmers who tried to farm corn hybrid varieties Bisi-2. In the village of Jayamandiri, District Cibugel, Sumedang regency. Mechanical determination of the respondent farmers used was simple random sample (Simple Random Sampling) with 45 farmers (respondent) .The Effect between factors of production with a production produced, tested by analysis of variance (Analysis of Variance / ANOVA). Tests carried out using SPSS 17. The influence of the factors of production with theresults of the simultaneous production was a factor of production land, seed, fertilizer urea, Phonska, manure, and labor provide significant effect on yield. Judging from the effect between factors of production with partial production, production factors which influence the results of seed production is a factor of production and labor.